Quality assessment of heatstroke videos on TikTok - Qiu, Jun; Zhou, You-Lian (Frontiers in Public Health, 2024)
Background The prevalence of heatstroke is rising due to global warming, making it a serious but preventable condition, highlighting the urgent need for effective dissemination of relevant health education to the general public. Advances in technology have made accessing health information more convenient and rapid. In recent years, short videos have become a primary medium for delivering health education, with TikTok gaining considerable popularity among the general public. However, the quality of heatstroke-related health education content on TikTok deserves closer scrutiny. Objective This study aimed to evaluate the quality and content of heatstroke-related videos available on TikTok. Methods The present study analyzed the top 100 heatstroke-related short videos on TikTok, focusing on their characteristics, quality, and the content they conveyed. The quality of these videos was assessed using the DISCERN instrument. In addition, the completeness of the videos was assessed by examining six key aspects: disease definition, clinical manifestations, risk factors, assessment, management, and outcomes. Results The study included a total of 90 videos. The results showed that news organizations and healthcare professionals were the primary contributors to these videos, with those from news organizations receiving the most attention. In contrast, those from healthcare professionals received comparatively less engagement. Overall, the quality of the information was found to be moderately low, with the highest quality videos posted by non-profit organizations, followed by those posted by healthcare professionals. The majority of videos uploaded described the disease definition, clinical presentation, risk factors, assessment, management, and outcomes of heatstroke. Conclusion The quality of information provided in heatstroke-related short videos on TikTok is generally inadequate and requires significant improvement. In addition, such content should be subject to government review to ensure its accuracy and reliability.